Association of vascular and inflammatory markers with metabolic disorders in women with polycystic ovary syndrome - Atanasova Boshku, Aleksandra; Ivanova Panova, Daniela; Zafirova Ivanovska, Beti (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The prevalence of metabolic disorders, obesity and insulin resistance in women with polycystic ovary syndrome (PCOS) occur early in life and places this group at risk of cardiovascular disease. Hyperhomocysteinemia and increased C-reactive protein (CRP) activity have an effect on promoting atherosclerosis. This study was designed to evaluate whether high sensitivity (hs-CRP) and homocysteine (Hcy) are elevated in PCOS and to elucidate their possible relation to obesity, insulin resistance, or metabolic changes usually present in women suffering from PCOS. Methods. Serum concentration of hs-CRP and plasma levels of Hcy were evaluated in 73 PCOS women and 43 healthy women, together with clinical, anthropometric and hormonal parameters. Results. The mean of body mass index (BMI), waist circumference (WC), waist to hip ratio and mean concentration of luteinizing hormone (LH), testosterone, androstenedione, free androgen index, fasting insulin, homeostatic model assessment of insulin resistance (HOMA- IR), hs-CRP and Hcy were significantly higher in PCOS women compared to age-matched healthy women. There was a positive correlation between hs-CRP and BMI, WC, insulin, triglycerides (p < 0.001) and significant negative correlation with LH, sex hormone binding protein (SHGB), HOMA-IR, high density lipoprotein cholesterol (HDL-C) (p < 0.001). The Hcy concentration had a significant negative correlation with HDL-C level (p < 0.05). The present study demonstrated increased mean concentration of Hcy in hs-CRP women with PCOS. Conclusion. Our results support the use of these biomarkers in the evaluation of potential risk for cardiovascular diseases and early prognosis and treatment implications.